PENGARUH RELIGIUSITAS DAN KEGIATAN SPIRITUAL TERHADAP PERSEPSI TINGKAT KEAMANAN DI INDONESIA - Zaki Abdullah; Hasse Jubba (Jurnal Studi Agama dan Masyarakat, 2020)
Both religiosity and spiritual activities could improve security perceptions by reducing crime rates in Indonesia. However,  this did not apply to minorities because of the possibility of religious discrimination. This study intended to determine the influence of religiosity and spiritual activities on the security perceptions of religious adherents in Indonesia, namely Islam, Protestantism, Catholicism, Hinduism and Buddhism using secondary data obtained from the Indonesian Family Life Survey of 32,466 individuals. The finding revealed that religiosity had a positive and significant effect on the sense of security of all adherents except Buddhist followers. Meanwhile, spiritual activities had a positive effect on security of adherents of Islam and Hinduism. In contrast, it negatively influenced Protestant, Catholic and Buddhist followers, since terrorism and discrimination against the worship places were frequently occured. Therefore, it was concluded that religiosity had a positive effect on  security of the followers of the majority religions; however, it negatively affected to the followers of minority religion. It meant that being the followers of religion majority was still dangerous for the followers of religion minority. This evidenced that there were still lack of religious tolerance in Indonesia.